Investigation of dynamic and vibrational parameters of anti-tank missile launchers using the "dynamic-reaction" launch principle - Bùi Đình Tân; Mai Duy Phương; Dương Quốc Việt (Journal of Military Science and Technology, 2024)
Anti-tank missiles are launched according to the "dynamic-reaction" principle, creating a high velocity for the missile in a short period of time, minimizing the recoil of the launch system. Because the launch phase takes place in a very short time (size 0.02 s), the processes take place quickly, easily unbalanced, causing danger to the equipment and the gunner to shoot. The article proceeds to build a mathematical model describing the processes taking place in the launch phase, determining the dynamic parameters of the projectile and the launch system. This is the theoretical basis used for the design and manufacture of the launch system according to this principle. The application calculates the typical anti-tank missile prototype system.